Analisis Sistem Kerja UPS (Uninterruptible Power Supply) Power Scale 200 kVA Terminal Bandara PT. Angkasa Pura II (Persero): Analysis Of The 200 Kva Power In UPS (Unintrruptible Power Scale) System at The Airport Terminal Of PT. Angkasa Pura II (Persero) - Lorenza, Aldo (Institut Riset dan Publikasi Indonesia, 2021)
The higher the level of electricity consumption, the PLN (State Power Plant) as a provider of electricity andas a national electricity energy manager has the obligation to meet the national electrical energy needswhich are increasingly increasing. In order to avoid an undesirable thing, the electricity network is cut off atthe airport terminal which can endanger the safety, comfort and safety of prospective airplane passengers.So, UPS is used as an alternative electrical energy supplier to anticipate sudden power outages whilewaiting for an emergency generator to be activated (emergenci diesel generator). This report focuses ondiscussing how long UPS can back up the Airport Terminal load without an emergency generator which isdone using the observation method in the field. The results of the observations in the field were found that byusing a UPS, namely: 3) The level of efficiency of the AC - AC UPS at the Airport Terminal is 95%, meaningthat the more power the source can provide by the Airport Terminal, this allows significant energy savings inevery work carried out at the airport, 5) The ability of the UPS to accommodate the transmitter system load,which is for 34.16 minutes, this time is more than enough to switch the power source to the generator set, 6)The UPS loads at the Airport Terminal by 60% (120 kVA is used from 200 kVA), more loads can still bedone, 7) UPS rating at the Airport Terminal has more power than the ideal UPS rating (oversizing UPS).This is done to get a longer runtime, if there are additional tools, and not all electronic devices are backedup by UPS.